The comparison of clinical and electroneuromyographic diagnosis [Klinik Tani ile Elektronöromiyografik Taninin karşilaş tirilmasi] - (:unkn) unknown (My University, 2004)
Electrodiagnostic investigations are important in reaching diagnosis and planning treatment. To achieve correct diagnosis with an electrodiagnostic test patient's clinical history, physical examination findings, and clinical diagnosis of the referring physician should be known. The aim of this study was to investigate the correlation between clinical and electroneuromyographic diagnoses of patients referred to our electroneuromyography (ENMG) laboratory. ENMG reports of 1585 patients were reviewed in this retrospective study. Patients' clinical and ENMG diagnoses were compared, and the reports were classified according to both diagnosis and frequency. Among the patients, 371 were men, 1214 were women. The mean age was 48±14.8 years (2 months-89 years). In 1272 patients, the clinical diagnoses were indicated in the report, however, in 312 were not. The most common clinical diagnosis was carpal tunnel syndrome (45.1%), polyneuropathy (13.9%), lumbar radiculopathy (13.1%) and cervical radiculopathy (10.8%). On the other hand, 43.3% of patients had normal results in the electrodiagnostic tests. The most common ENMG diagnosis was carpal tunnel syndrome (27.4%), the others were lumbar radiculopathy (8.3%), and polyneuropathy (7.5%). The clinical diagnosis was correlated with the ENMG diagnosis in 42.3% of reports while, there was a difference between clinical and ENMG diagnosis in 38% and the clinical diagnosis were not given in the remaining reports. The patients must be clinically evaluated in detail and, electromyographer should be informed about the patient history, clinical diagnosis and physical examination findings before referring to ENMG laboratory. In this way, we can obtain an efficient use of the ENMG tests.
Keywords: Carpal tunnel syndrome; Clinical diagnosis; Electroneuromyographic diagnosis; Electroneuromyography (ENMG)